“100 metros rasos”: objeto de aprendizagem para o ensino de física como aplicação do conectivismo e do edutretenimento - Santos, João Fernando Tobgyal da Silva [UNESP] (2016)
This thesis contains a Learning Object proposal in a case of physics, Rectilinear Motion Uniform, exemplified in a hypothetical situation of a proof of athletics - 100 meters, to constitute an application of the concepts of Connectivism and Edutretenimento. The reflections brought by observing the behavior of students in the classroom, increasing access to new technologies, the concerns of this research, readings and applications in the classroom, notes the presence of these mobile technologies in the daily lives of students, in and out of rooms class without proper empowerment of these, for the sake of learning. The spread of applications, programs and systems in a range of ease of use, offers resources focused on the users' wellbeing. It serves as an object of study, an application proposal, contributed the principles of Connectivism and Edutretenimento, which proposes the construction of knowledge in school. It is used to Gowin V methodology to the key question of the definition and the driving line of the present dissertation thinking. It is expected to contribute effectively to the development of tools, which when made available to teachers and students of the Brazilian education system, boost European ease of use, applicability and efficiency in teacher-student relationship, strengthening education and interest in the study of Sciences.